AESTHETIC EDUCATION IN THE NEW MEDIA ERA: FROM THE PERSPECTIVE OF AESTHETIC EDUCATION PHILOSOPHY - Yong, ZHAO (European journal for philosophy of religion, 2023)
Aesthetic education plays an important role in people's education and training. Guided by Marxist aesthetic education view, studying the construction of aesthetic education in the new era is not only an important condition for shaping a sound personality and an inevitable requirement for guiding people's better life in the new era, but also a theoretical basis for guiding the cultivation of innovative talents in the new era, and a realistic need for dealing with the misunderstanding of aesthetic education in the new era. As an important part of socialist cultural construction, aesthetic education can cultivate people's perception, acceptance and creativity of beauty, shape individual's lofty ideals and sentiments by purifying the soul and casting the soul, transform the objective world and beautify the subjective world according to the law of beauty, establish a beautiful world outlook, outlook on life and values, and promote people's quality promotion and all-round development. From the perspective of aesthetic education, we media's own characteristics enable it to become a platform for teachers' teaching and students' learning at the same time, and with the new changes shown by the relationship between the media and the audience, we media can become an effective carrier to enhance college students' aesthetic education, providing us with a good opportunity to effectively enhance college students' aesthetic education.